Improved dietary diversity of school adolescent girls in the context of urban Northwest Ethiopia: 2017 - Birru, Samuel Mersha (Ital J Pediatr, 2018)
BACKGROUND: Undiversified diet increases the vulnerability of adolescents for different nutritional problems. Therefore, this study assessed dietary and associated factors among school adolescent girls in Gondar city, northwest Ethiopia. METHODS: A cross-sectional study was conducted from March to April 2017. Simple random sampling technique was used to select 778 adolescent school girls. A structured questionnaire was used to collect data. Multivariable logistic regression analysis was fitted to identify significant factors of dietary diversity. Adjusted Odds Ratio (AOR) with 95% confidence interval was used to show the strength of association, while a P-value< 0.05 of was used to declare the significance of association. RESULTS: This finding indicated that adolescent girls who met minimum dietary diversity with were 75.4% (95%CI (72.3, 78.6). School type (AOR = 3.17, 95%CI: 1.90, 5.28) and residence (AOR = 2.0, 95%CI: 0.84, 3.01) were significantly associated with adequate dietary diversity. CONCLUSIONS: Dietary practice of adolescent girls is good in Gondar City Administration. School type and residence of adolescents were significantly associated with minimum dietary diversity. Thus, Special attention needs to be paid on government school and rural adolescents to improve the intake of variety diet.